2021
DOI: 10.51685/jqd.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Connective Effervescence and Streaming Chat During Political Debates

Abstract: Recent advancements in online streaming technologies have re-centered the audience as an important part of live broadcasts, including live political events. In fall 2020, each of the U.S. presidential and vice presidential debates were streamed on a number of online platforms that provided an integrated streaming chat where the public could comment in real-time alongside the live debate video. Viewers could simultaneously tune into what the candidates were saying and see what a sample of their peers thought ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…On the other hand, the content of expression matters for democratic norms of non-violence and racial equality and the role of social position in breaking the norms. First, we found a high level of aggressive and threatening content, including open calls for violence, consistent with studies of live digital comments in election contexts (Ventura et al 2021). As expected, we also found asymmetries in racial hostility, with derogation against Blacks as a group far more prevalent than derogation against whites.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the content of expression matters for democratic norms of non-violence and racial equality and the role of social position in breaking the norms. First, we found a high level of aggressive and threatening content, including open calls for violence, consistent with studies of live digital comments in election contexts (Ventura et al 2021). As expected, we also found asymmetries in racial hostility, with derogation against Blacks as a group far more prevalent than derogation against whites.…”
Section: Discussionsupporting
confidence: 89%
“…DeKoster and Houtman (2008) note how these online communities construct racist attitudes and social action. More broadly, Ventura and colleagues (2021) identify a high rate of toxic and insulting comments on digital live streams of presidential debates on Facebook news pages. Hmielowski, Hutchens, and Cicchirilo (2014) examine the normative acceptability of aggression in online political message boards, finding that the prevalence of “online flaming” leads users to accept heightened aggression.…”
Section: Hateful and Aggressive Online Rhetoricmentioning
confidence: 99%
“…Prior studies have shown consistently that toxicity exists online (Ventura et al 2021;Chen 2017;Coe et al 2014;Muddiman & Stroud 2017;Sobieraj & Berry 2011;Oz et al 2018;Papacharissi 2004;Theocharis et al 2016). However, the severity of online toxicity/incivility seems to vary considerably across different studies depending on the platform examined, the definition of civility used, and the measurement approach (e.g., Chen 2017;Sobieraj & Berry 2011).…”
Section: Evidence Of Online Toxicitymentioning
confidence: 99%
“…The Perspective API was found to accurately detect toxicity when compared against human coders' classification of comments on Reddit (Rajadesingan et al 2020), the New York Times (Muddiman et al 2019), and Facebook and Twitter (Hopp et al 2020). The API has been used to detect toxicity on various social media platforms (e.g., Hopp et al 2020;Rajadesingan et al 2020), including Facebook comments in particular (Ventura et al 2021;Hopp et al 2020). This measure serves as the primary dependent variable in our analyses below.…”
Section: Comment Toxicitymentioning
confidence: 99%
See 1 more Smart Citation